2018
DOI: 10.4103/jispcd.jispcd_31_18
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and practices related to Hepatitis B infection among dental and oral hygiene students at a university in Pretoria

Abstract: Aims and Objectives:The aim of the study was to determine the knowledge and practices of dental and oral hygiene (OH) students related to the transmission and prevention of the hepatitis B virus (HBV).Methods:A cross-sectional analytical design was used and all dental and OH students registered at a university in Pretoria in 2017 were asked to participate. Students were classified as either clinical (senior students who were treating patients) or nonclinical (junior students who had not yet started treating pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…Almost similar results were reported in other studies [23,24,25,26,27]. However, dental and oral hygiene students had good knowledge regarding HBV infection and its prevention [28]. Also, good knowledge of the risk factors for HBV infection and awareness of HBV vaccine among medical students were reported in Cameroon [29].…”
Section: Discussionsupporting
confidence: 84%
“…Almost similar results were reported in other studies [23,24,25,26,27]. However, dental and oral hygiene students had good knowledge regarding HBV infection and its prevention [28]. Also, good knowledge of the risk factors for HBV infection and awareness of HBV vaccine among medical students were reported in Cameroon [29].…”
Section: Discussionsupporting
confidence: 84%
“…From this study, it emerged that oral piercings can represent a risk to oral health, as found by Maitland I et al [19]. There is a widespread lack of awareness regarding the complications and correct methods of maintaining oral piercings, as confirmed in the literature, among dental students [20]. Compared to our previous study on adolescents and young adults [6], lack of knowledge was surveyed among older individuals, comparing results of questionnaires to patients wearing oral piercings and directly visited.…”
Section: Discussionmentioning
confidence: 61%
“…Blood transmission, a signi cant route of HBV infection as well as sexual transmission, should not be neglected. In addition, one-fth of participants in our study were detected sharing personal hygiene products like toothbrushes and/or towels, which would amplifythe possibility of HBV infection through the broken skin [31]. Therefore, health educationtargeting those issues need to be enhanced with migrant workers.…”
Section: Discussionmentioning
confidence: 96%